Antispasmodic Effects of Aqueous and Hydroalcoholic Punica granatum Flower Extracts on the Uterus of Non-pregnant Rats - Ahangarpour, Akram; Heidari, Razieh; Abdolahzadeh, Mahsa; Oroojan, Ali Akbar (Journal of Reproduction & Infertility, 2012)
Background: Punica granatum Linn. (PG) is native to the Mediterranean region. Its flower exhibited antioxidant activity. The present study attempt to investigate the effect of these extract on uterine contraction and its possible mechanism(s). Methods: Thirty five female Wistar rats (200-300 g) at estrous phases of cycle was examined in this study; pieces of virgin adult rat uterus (1.5 cm) were suspended in an organ bath containing 10 ml of De Jalon solution at 29 °C. Tissue contractility was isometrically recorded. KCl (60 mM), BaCl2 (4 mM) and oxytocin (10 mU/ml) were applied to the tissue in the presence and absence of aqueous and hydroalcoholic extracts of the plant (0.05, 0.1, 0.2, 0.4 and 0.8 mg/ml). Propranolol (1 µM) and naloxane (1 µM) were added in KCl induced contractions. The results were analyzed by ANOVA and p<0.05 were considered as significant. Results: Cumulative concentration of extracts reduced uterine contractions induced by KCl dose-dependently (p<0.01). Extracts in a dose dependent (p<0.05) reduced uterine contractions decreased dose-dependently after of addition oxytocin. The extracts added cumulatively to the organ bath reduced contractions but they did not affect uterine contractions induced by BaCl2 except the last dose. Spasmolytic effects of the extracts were not affected by propranolol or naloxane in KCl induced contractions. Conclusion: Extracts diminished K+-induced contraction in uterus, therefore it seems that substances that decrease K+-induced contraction can also block voltage dependent calcium channel. The extracts did not have any effect on β-adrenoceptors or potassium channels.
Keywords: Naloxane; Oxytocin; Propranolol; Punica granatum flower; Uterus